Constant-temperature heating membrane for enhancing reproducibility of PTC (Positive Temperature Coefficient) effect as well as preparation method and application thereof
By using technical means to form fine phase regions and dopant conductive fillers in PTC heating films using crosslinking reactions in PTC heating films, the problems of insufficient PTC effect and poor reproducibility in low-temperature environments are solved, and higher reproducibility and cycle life of PTC effect are achieved.
Patent Information
- Application Number
- CN202411857283.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing PTC heating film only occurs when it reaches the near the melting point of the polymer, resulting in rapid loss of the polymer during multiple uses. The polymer melting point is generally high, so it cannot be suitable for normal low temperature environments, and the reproducibility of the PTC effect is poor.
A constant temperature heating diaphragm consisting of two insulating isolation layers, copper electrodes and a positive temperature coefficient coating is adopted. The positive temperature coefficient coating contains 15-30 wt% thermoplastic polyurethane elastomer, 5-20 wt% secondary phase matrix, 10-40 wt% organic phase change material, 14-25 wt% first conductive filler, 1-5 wt% second conductive filler, 0.1-1 wt% defoaming agent, 0.5-2 wt% thickener and 30-50 wt% organic solvent. The fine phase region is formed through crosslinking reaction and conductive filler of different sizes is doped to inhibit the agglomeration of the conductive filler.
It significantly enhances the reproducibility of the PTC effect, improves the cycle life of the heating film, ensures a large PTC strength, a small NTC strength and flexibility, so that the resistivity value of the heating film is 1-50Ω·cm at room temperature, and is suitable for temperature-controlled parts of various shapes.
Smart Images

Figure CN119521475A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heating materials, and in particular relates to a constant temperature heating diaphragm with enhanced PTC effect reproducibility, and a preparation method and application thereof. Background Art
[0002] Heating film with positive temperature coefficient (PTC) effect is a new type of functional material. It has attracted wide attention due to its good processability and excellent conductivity. Generally, the heating function can be achieved by adding conductive fillers. Positive temperature coefficient materials are very sensitive to temperature. When the temperature rises to a certain temperature (Curie temperature point), the resistivity of the material will increase sharply, and the heating power will drop rapidly, thereby achieving the function of temperature control heating or closed circuit. Due to the special properties of positive temperature coefficient materials, they have important application value in the fields of sensors, circuit protection, temperature control heating, etc.
[0003] Chinese invention patent CN103476158B discloses a PTC composite heating film and its preparation method and application. The PTC composite heating film is stacked in sequence by a first polymer cured sheet, a PTC composite layer and a second polymer cured sheet. The first polymer cured sheet and the second polymer cured sheet are both epoxy resins, and the PTC composite layer is composed of 10-80 parts of polymer, 20-90 parts of conductive particles and 1-10 parts of additives according to mass fraction. The polymer is at least one of polyamide, polyethylene, polypropylene, polyvinylidene fluoride, polytrifluorochloroethylene, epoxy resin and polyimide. The conductive particles are at least one of carbon black, graphite powder, carbon fiber powder, metal powder, carbon nanotubes and graphene. The principle of the PTC composite heating film is that after the crystalline or semi-crystalline polymer is filled with conductive particles, due to the thermal expansion effect of the matrix itself or the crystal phase structure transformation effect, the PTC effect is generated to achieve intelligent temperature control. However, the heating film prepared by this technology will only produce the PTC effect when it reaches near the melting point of the polymer, which will cause the polymer to be consumed faster during multiple uses. In addition, the melting point of polymers is generally high, which makes the Curie temperature of the PTC composite material high and cannot be used in normal low temperature environments.
[0004] Chinese invention patent application CN112770422A discloses a self-controlling temperature heating film and its preparation method and application, which is composed of an insulating isolation layer, a positive temperature coefficient coating and an insulating protective layer. The insulating isolation layer and the insulating protective layer have the same raw material composition, both of which are composed of insulating polymers and heat-insulating nanoparticles / thermal conductive functional nanoparticles. The positive temperature coefficient coating is composed of 20-40wt% nano-conductive filler, 10-30wt% positive temperature coefficient thermistor filler, 10-30wt% polymer and the remainder phase change material. The nano-conductive filler is at least one of graphene, conductive carbon black, carbon nanotubes, nano-graphite powder, nano-metal powder and nano-metal wire. The positive temperature coefficient thermistor material is at least one of ethylene-vinyl acetate copolymer, positive temperature coefficient ceramic powder, polycaprolactone, biochip paraffin, and thermoplastic polyurethane elastomer. The polymer is at least one of silicone rubber, epoxy resin, thermoplastic elastomer, styrene-butadiene rubber and polyurethane. The phase change material is at least one of low-temperature lubricating oil, low-temperature grease and paraffin. However, the self-controlling temperature heating film prepared by this technology needs to be improved in terms of application repeatability. The PTC effect in its durability performance curve only occurs 20 times, which cannot indicate that the self-controlling temperature electric heating film has good stability in use. Summary of the invention
[0005] In view of the problem of poor reproducibility of PTC effect in existing PTC heating films, the primary purpose of the present invention is to provide a constant temperature heating film and its preparation method which has a simple and safe preparation process, greater PTC strength, smaller NTC strength and flexibility, and can significantly enhance the reproducibility of PTC effect.
[0006] Another object of the present invention is to provide the application of the constant temperature heating diaphragm with enhanced reproducibility of PTC effect in the preparation of temperature control components.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A constant temperature heating diaphragm for enhancing the reproducibility of PTC effect, comprising two insulating isolation layers, a copper electrode arranged between the insulating isolation layers, and a positive temperature coefficient coating, wherein the copper electrode is etched on the upper end of the lower insulating isolation layer, and the positive temperature coefficient coating is coated on the upper end of the copper electrode; the positive temperature coefficient coating comprises the following components: 15-30wt% thermoplastic polyurethane elastomer, 5-20wt% secondary phase matrix, 10-40wt% organic phase change material, 14-25wt% first conductive filler, 1-5wt% second conductive filler, 0.1-1wt% defoamer, 0.5-2wt% thickener, and 30-50wt% organic solvent; the secondary phase matrix is one of isocyanates, peroxides, polyhydroxy compounds, and epoxy compounds; the particle size of the first conductive filler is 100-300nm, and the particle size of the second conductive filler is 5-50um.
[0009] To further achieve the purpose of the present invention, preferably, the isocyanates are diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI) and hexamethylene diisocyanate (HDI); the peroxides are dibenzoyl peroxide (BPO) and diisophorone peroxide (DCP); the polyhydroxy compounds include glycerol, ethylene glycol and polyethylene glycol (PEG); and the epoxy compound is epoxy resin.
[0010] Preferably, the organic phase change material is at least one of paraffin, fatty acid and polyol.
[0011] Preferably, the fatty acid is stearic acid, palmitic acid, myristic acid, lauric acid; and the polyol is polyethylene glycol, tetradecanol.
[0012] Preferably, the first conductive filler is at least one of conductive carbon black and metal powder; the second conductive filler is at least one of carbon nanotubes, carbon fibers and graphene.
[0013] Preferably, the defoaming agent includes at least one of silicone oil defoaming agent, polyvinyl alcohol defoaming agent or polyester defoaming agent; the thickener is at least one of ethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the organic solvent is at least one of toluene, xylene, isophorone, n-hexane and acetone.
[0014] Preferably, the two insulating isolation layers are both polyimide films; the thickness of the insulating isolation layer is 0.5-2mm; the thickness of the positive temperature coefficient coating is 0.5-2mm; the resistivity of the constant temperature heating film for enhancing the reproducibility of the PTC effect is 1-50Ω·cm at room temperature.
[0015] The method for preparing the constant temperature heating film for enhancing the reproducibility of the PTC effect comprises the following steps:
[0016] S1, adding a thermoplastic polyurethane elastomer into an organic solvent, and stirring and dispersing the thermoplastic polyurethane elastomer into an organic solvent until the elastomer is free of particles;
[0017] S2, adding the secondary phase matrix to the product obtained in step S1, heating in a water bath and stirring for cross-linking reaction for 1-2 hours;
[0018] S3, adding the organic phase change material, the first conductive filler and the second conductive filler to the product obtained in step S2 and stirring and mixing them evenly;
[0019] S4, adding the defoamer and thickener to the mixed solution of step S3, stirring and dispersing them evenly;
[0020] S5, using a coating machine to coat the mixed solution obtained in step S4 on the lower insulating isolation layer with a copper electrode etched on the upper end, and drying;
[0021] S6. The lower insulating isolation layer and the upper insulating isolation layer are heat-pressed and packaged to obtain a constant temperature heating film with enhanced reproducibility of the PTC effect.
[0022] Preferably, in steps S1-S4, the stirring is mechanical stirring, the speed is 1000-2400rmp, and the temperature is 60-90°C; wherein the time for stirring and dispersing in step S1 until there are no particles in the solvent is 30-60min; the time for stirring in step S3 is 30-60min; the time for stirring in step S4 is 20-30min;
[0023] The temperature of the hot pressing bonding is 60-100° C. and the pressure is 0.5-1 MPa.
[0024] The application of the constant temperature heating diaphragm with enhanced reproducibility of PTC effect in the preparation of temperature control components.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial technical effects:
[0026] (1) The positive temperature coefficient coating provided by the present invention not only forms a finer phase region by adding a secondary phase matrix through cross-linking, but also dopes conductive fillers of different sizes during the cross-linking process to improve the agglomeration of the conductive fillers during recycling.
[0027] (2) The present invention constructs a cross-linked phase region through a two-phase matrix to limit the size of filler aggregates, and adopts a mixture of fillers of different sizes to reduce the contact probability between fillers of the same type, so that the tendency of filler agglomeration is suppressed. Under the synergistic effect of the two-phase matrix and the mixed filler, not only the movement range of the conductive filler is limited but also the agglomeration behavior of the same filler is reduced, further solving the problem of filler migration and agglomeration in the long-term use of the PTC heating film.
[0028] (3) The cross-linking treatment adopted in the present invention is carried out during the preparation process and is a low-cost chemical cross-linking method. It does not have the disadvantages of high cost and high equipment requirements like radiation cross-linking and other methods.
[0029] (4) The main phase matrix used in the present invention is a thermoplastic polyurethane elastomer, which has extremely strong flexible support and can be bent at will, and has broad application prospects.
[0030] (5) The PTC heating film prepared by the present invention can be cut into shapes according to the purpose and can be widely used in various regular and irregular shaped substrates, such as the supply of temperature control components for household and industrial electrical appliances, daily indoor and outdoor heat preservation and heating, etc.
[0031] (6) Since the resistivity value at room temperature is relatively small, the PTC heating film of the present invention can reach the equilibrium temperature within 100 seconds within the safety voltage range of 6-36V, and has the advantages of fast heating and uniform heating. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the 100-time power-on-temperature rise curve of the PTC heating film obtained in Example 1;
[0033] Figure 2 This is a diagram showing uniform heating of the surface of the PTC heating film obtained in Example 1 after the film is energized and heated 100 times;
[0034] Figure 3 This is a PTC characteristic diagram of the PTC heating film obtained in Example 1 after 700 high and low temperature shock cycles;
[0035] Figure 4 This is a comparison diagram of the resistance-temperature curves of the PTC heating film obtained in Example 1 before and after bending 10 times;
[0036] Figure 5 The power-on-temperature rise curves of the PTC heating film obtained in Example 1 at different voltages.
[0037] Figure 6 This is a PTC characteristic diagram of the PTC heating film obtained in Example 2 after 500 high and low temperature shock cycles;
[0038] Figure 7 This is a PTC characteristic diagram of the PTC heating film obtained in Example 3 after 500 high and low temperature shock cycles;
[0039] Figure 8 This is a PTC characteristic diagram of the PTC heating film obtained in Example 4 after 500 high and low temperature shock cycles;
[0040] Fig. 9 This is the 60-time power-on-temperature rise curve of the PTC heating film obtained in Comparative Example 1;
[0041] Fig.10 This is a diagram showing uniform heating of the surface of the PTC heating film obtained in Comparative Example 1 after 60 times of power-on heating;
[0042] Fig.11 This is a SEM comparison diagram of the PTC heating films obtained in Comparative Example 1 and Example 1. DETAILED DESCRIPTION
[0043] In order to better understand the present invention, the present invention is further described below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0044] In the prior art, conductive particles are usually added to the matrix resin, or phase change materials are added to make electric heating slurry, which is then coated on the insulating layer and then connected to electrodes to make a PTC heating film. The main problem with such a PTC heating film is that the PTC effect has poor reproducibility and low repeatability during application.
[0045] The reproducibility of the PTC effect is based on the complete reversibility of the deconstruction and reconstruction of the conductive network within the material. However, the thermodynamic incompatibility between the polymer matrix and the conductive filler makes it very easy for the conductive filler to aggregate in the molten state to form obvious clusters. When the aggregates are large, they are difficult to break, and the conductive network cannot be restored to its original state, resulting in a weakened PTC effect of the composite material.
[0046] The present invention finds that when the particle size of the first conductive filler is 100-300nm, the particle size of the second conductive filler is 5-50um, and the secondary phase matrix includes one of isocyanates, peroxides, polyols and epoxy compounds, the thermoplastic polyurethane elastomer and the secondary phase matrix can undergo a crosslinking reaction to form a fine phase region, thereby inhibiting the conductive filler from forming large aggregates. Specifically, isocyanates react with amino or hydroxyl groups in the thermoplastic polyurethane elastomer to form urea or carbamate groups (-NHCOO-) to connect, thereby crosslinking the chain. Peroxides decompose at a certain temperature to generate free radicals, which can react with monomers or molecules in the thermoplastic polyurethane elastomer chain, resulting in crosslinking between polymer chains. The hydroxyl groups (-OH) in the polyols react through esterification, and the epoxy groups (-CO-) in the epoxy compounds react through addition reactions with functional groups (amino, hydroxyl, etc.) in the thermoplastic polyurethane elastomer to form a crosslinked network structure. Such a cross-linked network structure is combined with the above two different sizes of fillers, so that the cross-linked network structure can be formed to limit the range of motion of the two different sizes of fillers, thereby reducing the size of the aggregates. At the same time, the fillers in the above two particle size ranges can improve the dispersibility and reduce the probability of agglomeration of the same fillers. Under the synergistic effect of the cross-linked structure and the mixed filler, the random migration and agglomeration of the conductive filler at high temperature are greatly suppressed, and the reversibility of the deconstruction and reconstruction of the conductive network is improved, thereby improving the cycle life of the PTC heating film. Moreover, the thermoplastic polyurethane elastomer is mainly used as a supporting material to maintain the overall flexibility of the diaphragm, while encapsulating the phase change material and the conductive filler to prevent leakage. The addition of the phase change material in the present invention is that the positive temperature coefficient coating undergoes a phase change after reaching a certain temperature, so that the conductive network inside the material breaks, the resistivity increases sharply, and the PTC effect is produced, which is the core function of the general phase change material. The addition of the defoamer in the present invention can avoid the bubbles generated during the preparation from affecting the film-forming effect, which is also the main function of the general defoamer. The addition of the thickener in the present invention can increase the viscosity of the mixed solution, so that the composite material maintains a uniform and stable fluid state, and the film-forming state is better, which is also the main function of the general thickener.
[0047] Based on the above findings, the present invention develops a constant temperature heating film with enhanced reproducibility of PTC effect, which can not only ensure greater PTC strength, smaller NTC strength and softness, but also inhibit the agglomeration of conductive fillers to maintain the reproducibility of PTC effect. The core technical measure of the present invention is to provide a constant temperature heating diaphragm with enhanced reproducibility of PTC effect, which is composed of two insulating isolation layers, a copper electrode and a positive temperature coefficient coating arranged between the insulating isolation layers. The copper electrode is etched on the upper end of the lower insulating isolation layer, and the positive temperature coefficient coating is coated on the upper end of the copper electrode; the positive temperature coefficient coating includes the following components: 15-40wt% thermoplastic polyurethane elastomer, 5-25wt% secondary phase matrix, 20-50wt% organic phase change material, 14-25wt% first conductive filler, 1-5wt% second conductive filler, 0.1-1wt% defoamer, 0.5-2wt% thickener, 30-50wt% organic solvent; the secondary phase matrix is one of isocyanates, peroxides, polyhydroxy compounds and epoxy compounds; the particle size of the first conductive filler is 100-300nm, and the particle size of the second conductive filler is 5-50um.
[0048] It should be noted that the constant temperature heating diaphragm of the present invention is composed of two insulating isolation layers and a copper electrode and a positive temperature coefficient coating arranged between the insulating isolation layers. The copper electrode etched on the upper end of the lower insulating isolation layer plays a role in providing positive and negative poles, and it can only be powered on and generate heat when connected to a power source; the two insulating isolation layers encapsulate the positive temperature coefficient coating and the copper electrode. The constant temperature heating diaphragm with enhanced reproducibility of the PTC effect of the present invention can be cut into shapes according to the purpose, and is widely used in various regular and irregular shaped substrates, such as the supply of temperature control components for household and industrial appliances, daily indoor and outdoor insulation and heating, etc. Specifically, such as a series of insulation and heating scenarios such as electronic equipment startup protection components under cold conditions, active thermal control systems for equipment, wearable insulation fabrics, indoor floor heating, etc.
[0049] In the present invention, the test method of the thermal shock cycle curve uses the GB / T2423.34-2024 standard to perform a rapid temperature change test. The purpose of this test is to determine the change in the PTC effect of the PTC heating film after multiple high and low temperature environment alternations.
[0050] The test method of power-on-temperature rise curve is based on GB / T29470-2012 standard. The purpose of this test is to examine the heating stability and adaptive thermal control function of PTC heating film.
[0051] The uniform heating performance of the film is tested with reference to GB / T7287-2008 standard. The test method is to use an infrared thermal imaging camera to observe the surface temperature field of the PTC heating film after it reaches a balanced state when the power is turned on and the temperature is increased. The purpose of this test is to observe whether the PTC heating film heats evenly when the power is turned on.
[0052] The test method of resistance-temperature curve is based on GB / T29470-2012 standard. The purpose of this test is to observe the resistance change and PTC characteristics of PTC heating film under temperature change, so as to judge its PTC strength.
[0053] Example 1
[0054] A constant temperature heating film for enhancing the reproducibility of a PTC effect comprises the following components in percentage by mass: 20 wt% of a thermoplastic polyurethane elastomer, 10 wt% of a secondary phase matrix, 20 wt% of an organic phase change material, 17 wt% of a first conductive filler, 1 wt% of a second conductive filler, 0.5 wt% of a defoamer, 1.5 wt% of a thickener, and 30 wt% of an organic solvent; wherein the secondary phase matrix is glycerol, the phase change material is lauric acid, the first conductive filler is carbon black with a size of 100-200 nm, the second conductive filler is a carbon nanotube with a size of 30-50 um, the defoamer is polydimethylsiloxane, the thickener is sodium carboxymethyl cellulose, and the organic solvent is isophorone.
[0055] A method for preparing a constant temperature heating film for enhancing the reproducibility of a PTC effect comprises the following steps:
[0056] S1. Weigh 16 g of thermoplastic polyurethane elastomer and add it to 48 ml of isophorone. Disperse it with mechanical stirring until there are no particles in the solvent. The stirring time is 45 min.
[0057] S2, weigh 8g of propylene glycol, add it, and mechanically stir it under water bath heating to make it fully cross-linked with the thermoplastic polyurethane elastomer obtained in step S1, and the reaction time is 1h;
[0058] S3, weighing 16 g of lauric acid, 13.6 g of carbon black and 0.8 g of carbon nanotubes, adding them to the product obtained in step S2, and mixing them by high-speed mechanical stirring for 30 min;
[0059] S4, weighing 0.4g of polydimethylsiloxane and 1.2g of sodium carboxymethyl cellulose and adding them to the mixed solution obtained in step S3 in sequence, adjusting the viscosity of the solution to make it smooth, and mechanically stirring and dispersing until it is completely uniform, and the stirring time is 25min;
[0060] S5, using a coating machine to coat the mixed solution obtained in step S4 on the polyimide film containing the copper electrode, i.e., the lower layer of the insulating isolation layer, to obtain a positive temperature coefficient coating after drying, and the coating thickness is controlled to be 1 mm;
[0061] S6. The lower insulating isolation layer and the upper insulating isolation layer containing the positive temperature coefficient coating are hot pressed and packaged to obtain a PTC heating film; wherein the single layer thickness of the insulating isolation layer is 0.5 mm, and the hot pressing treatment process is: hot pressing temperature 80°C, pressure 1MPa.
[0062] In the above steps, the speed of mechanical stirring was 1800 rpm, the stirring temperature was 70° C., and the viscosity of the solution was adjusted to 1500 mPa`s.
[0063] In this embodiment, the thermoplastic polyurethane elastomer contains carbamate groups (-NH-COO-), which have strong reactivity. Under heating and stirring, the carbamate groups (-NH-COO-) will undergo esterification reaction with the hydroxyl groups (-OH) in glycerol to generate new ester bonds (hydroxy formate) and release water molecules at the same time.
[0064] R-OH+R'-NH-COO-→R-OCO-NH-R'+H2O
[0065] After the esterification reaction occurs, the amino groups in the thermoplastic polyurethane elastomer will connect with propylene glycol to form a cross-linked chemical structure. The cross-linked network formed by the two limits the range of motion of carbon black and carbon nanotubes, thereby reducing the size of the aggregates. In addition, the presence of two different-sized fillers can improve dispersibility and reduce the probability of agglomeration of the same filler. Therefore, under the synergistic effect of the cross-linked structure and mixed fillers, the random migration and agglomeration of the conductive filler at high temperature are greatly suppressed, and the reversibility of the deconstruction and reconstruction of the conductive network is improved, thereby increasing the cycle life of the PTC heating film.
[0066] The performance test of the PTC heating film of Example 1 was carried out, and the results are as follows: Figure 1-5 shown.
[0067] Figure 1 The PTC heating film obtained in Example 1 is powered on 100 times and the temperature rise curve; Figure 1 It can be seen that after 100 power-on and heating cycles, the equilibrium temperature of the PTC heating film dropped from 41.1°C to 40.9°C, with a temperature difference of only 0.2°C, indicating that a good heating equilibrium temperature can still be maintained after multiple cycles.
[0068] Figure 2 This is a diagram showing uniform heating of the surface of the PTC heating film obtained in Example 1 after 100 times of power-on heating; Figure 2 It can be seen that the surface heating uniformity of the PTC heating film at the 100th time is not much different from that at the 1st time.
[0069] Figure 3 The PTC characteristic diagram of the PTC heating film obtained in Example 1 after 700 high and low temperature shock cycles; Figure 3 It can be seen that the PTC heating film can still maintain a good PTC effect after 700 high and low temperature shock cycles.
[0070] Figure 4 The comparison of the PTC characteristics of the PTC heating film obtained in Example 1 before and after bending 10 times; Figure 4 It can be seen that after the PTC heating film was curled 10 times, the PTC characteristics of the film remained basically unchanged, indicating that the conductive network and structure within the material would not be destroyed by mechanical curling, showing good flexibility.
[0071] Figure 5 The temperature rise curve of the PTC heating film obtained in Example 1 under different voltages. Figure 5 It can be seen that whether at 6V or 24V, the PTC heating film exhibits excellent temperature control ability, and the equilibrium temperature is basically maintained around the phase change temperature of lauric acid, proving that it has a certain self-regulating function.
[0072] It can be seen from the above embodiments that the PTC heating film provided by the present invention has good flexibility, excellent PTC effect and repeatability, and broadens the application scope of the PTC heating film.
[0073] Example 2
[0074] A constant temperature heating film for enhancing the reproducibility of a PTC effect comprises the following components in percentage by mass: 25 wt% of a thermoplastic polyurethane elastomer, 5 wt% of a secondary phase matrix, 20 wt% of an organic phase change material, 13 wt% of a first conductive filler, 5 wt% of a second conductive filler, 0.3 wt% of a defoamer, 1.7 wt% of a thickener, and 30 wt% of an organic solvent; wherein the secondary phase matrix is diphenylmethane diisocyanate, the phase change material is paraffin, the first conductive filler is metal powder nickel powder with a size of 200-300 nm, the second conductive filler is carbon fiber with a size of 5-10 um, the defoamer is polyoxypropylene glycerol ether, the thickener is ethyl cellulose, and the organic solvent is isophorone.
[0075] A method for preparing a constant temperature heating film for enhancing the reproducibility of a PTC effect comprises the following steps:
[0076] S1. Weigh 15 g of thermoplastic polyurethane elastomer and add it to 36 ml of isophorone. Disperse it by mechanical stirring until there are no particles in the solvent. The stirring time is 40 min.
[0077] S2, weigh 3g of diphenylmethane diisocyanate, add it, and stir it mechanically under water bath heating to make it fully cross-linked with the thermoplastic polyurethane elastomer, and the reaction time is 1.5h;
[0078] S3, weigh 12g paraffin wax, 7.8g granular nickel and 3g carbon fiber, add them into S2, and mix them by high-speed mechanical stirring for 30min;
[0079] S4, weigh 0.18g of polyoxypropylene glyceryl ether and 1.02g of ethyl cellulose and add them to the mixed solution of S3 in sequence, adjust the viscosity of the solution to make it smooth, and disperse it with mechanical stirring until it is completely uniform, and the stirring time is 20min;
[0080] S5. Use a coating machine to coat the mixed solution obtained in step S4 on the polyimide film containing the copper electrode, that is, the lower layer of the insulating isolation layer, and obtain a positive temperature coefficient coating after drying. The coating thickness is controlled to be 1.5 mm.
[0081] S6. The lower insulating isolation layer containing the positive temperature coefficient coating and the upper insulating isolation layer are hot-pressed and packaged to obtain a PTC heating film; wherein the single-layer thickness of the insulating isolation layer is 1 mm, and the hot-pressing treatment process is: hot-pressing temperature 80°C, pressure 1MPa.
[0082] In the above steps, the rotation speed of the mechanical stirring was 1500 rpm, the stirring temperature was 90° C., and the viscosity of the solution was adjusted to 1500 mPa`s.
[0083] In this embodiment, the thermoplastic polyurethane elastomer contains active groups amino (-NH2) or hydroxyl (-OH), which have strong reactivity. Under heating and stirring, the amino (-NH2) or hydroxyl (-OH) will react with the isocyanate group (-NCO) of diphenylmethane diisocyanate by addition reaction.
[0084] R-NCO+R'-NH2→R-NH-C(=O)-NH-R'
[0085] R-NCO+R'-OH→R-NH-C(=O)-O-R'
[0086] After the addition reaction occurs, the amino or hydroxyl groups in the thermoplastic polyurethane elastomer will connect with diphenylmethane diisocyanate to form a cross-linked chemical structure. Consistent with Example 1, the cross-linked network structure formed by the dual-phase matrix limits the size of the aggregates formed, and the mixing of fillers of different sizes can improve the dispersibility and inhibit the same type of fillers from agglomerating. The synergistic effect of the two further enhances the reproducibility of the PTC effect of the heating film.
[0087] The PTC heating film of Example 2 was tested for cycle performance. The results are as follows: Figure 6 shown.
[0088] Figure 6 The PTC characteristic diagram of the PTC heating film obtained in Example 2 after 500 high and low temperature shock cycles; Figure 6It can be seen that the PTC heating film can still maintain a good PTC effect after 500 high and low temperature impact cycle tests, and the resistance-temperature curve does not change much, showing good reproducibility of the PTC effect.
[0089] Example 3
[0090] A constant temperature heating film for enhancing the reproducibility of a PTC effect comprises the following components in percentage by mass: 15wt% of a thermoplastic polyurethane elastomer, 5wt% of a secondary phase matrix, 30wt% of an organic phase change material, 15wt% of a first conductive filler, 3wt% of a second conductive filler, 0.5wt% of a defoamer, 1.5wt% of a thickener, and 30wt% of an organic solvent; wherein the secondary phase matrix is dibenzoyl peroxide, the phase change material is myristic acid, the first conductive filler is carbon black with a size of 100-200nm, the second conductive filler is a carbon nanotube with a size of 30-50um, the defoamer is polydimethylsiloxane, the thickener is hydroxyethyl cellulose, and the organic solvent is isophorone.
[0091] In an embodiment of the present invention, a method for preparing a constant temperature heating film for enhancing the reproducibility of the PTC effect comprises the following steps:
[0092] S1. Weigh 15 g of thermoplastic polyurethane elastomer and add it to 60 ml of isophorone. Disperse it with mechanical stirring until there are no particles in the solvent. The stirring time is 50 min.
[0093] S2, weigh 5g of dibenzoyl peroxide and add it, and stir it mechanically under heating in a water bath to make it fully cross-linked with the thermoplastic polyurethane elastomer, and the reaction time is 1h;
[0094] S3, weigh 30g of myristic acid, 15g of carbon black and 3g of carbon nanotubes, add them to S2, and mix them with high-speed mechanical stirring for 30min;
[0095] S4, weigh 0.5g of polydimethylsiloxane and 1.5g of hydroxyethyl cellulose and add them to the mixed solution of S3 in sequence, adjust the viscosity of the solution to make it smooth, and disperse it with mechanical stirring until it is completely uniform, and the stirring time is 25min;
[0096] S5. Use a coating machine to coat the mixed solution obtained in step S4 on the polyimide film containing the copper electrode, that is, the lower layer of the insulating isolation layer, and obtain a positive temperature coefficient coating after drying. The coating thickness is controlled to be 2 mm.
[0097] S6. The lower insulating isolation layer containing the positive temperature coefficient coating and the upper insulating isolation layer are hot-pressed and packaged to obtain a PTC heating film; wherein the single-layer thickness of the insulating isolation layer is 2 mm, and the hot-pressing treatment process is: hot-pressing temperature 90°C, pressure 1MPa.
[0098] In the above steps, the speed of mechanical stirring was 2000 rpm, the stirring temperature was 70° C., and the viscosity of the solution was adjusted to 1500 mPa`s.
[0099] In this embodiment, dibenzoyl peroxide decomposes under heating conditions to produce free radicals, which can cause the polymer chains in TPU to crosslink. Specifically, the free radicals produced by the decomposition of dibenzoyl peroxide can attack the carbon atoms on the TPU molecular chain, triggering a free radical chain growth reaction, resulting in the formation of new chemical bonds between the polymer chains, thereby achieving crosslinking. Consistent with Example 1, the cross-linked network structure formed by the two-phase matrix limits the size of the aggregates formed, and the mixing of fillers of different sizes can improve the dispersibility and inhibit the same filler from tending to agglomerate. The synergistic effect of the two further enhances the reproducibility of the PTC effect of the heating film.
[0100] The PTC heating film of Example 3 was tested for cycle performance. The results are as follows: Figure 7 shown.
[0101] Figure 7 The PTC characteristic diagram of the PTC heating film obtained in Example 3 after 500 high and low temperature shock cycles; Figure 7 It can be seen that the PTC heating film can still maintain a good PTC effect after 500 high and low temperature impact cycle tests, and the resistance-temperature curve does not change much, showing good reproducibility of the PTC effect.
[0102] Example 4
[0103] A constant temperature heating film for enhancing the reproducibility of a PTC effect comprises the following components in percentage by mass: 30 wt% of a thermoplastic polyurethane elastomer, 10 wt% of a secondary phase matrix, 15 wt% of an organic phase change material, 12 wt% of a first conductive filler, 2 wt% of a second conductive filler, 0.3 wt% of a defoamer, 0.7 wt% of a thickener, and 30 wt% of an organic solvent; wherein the secondary phase matrix is an epoxy resin, the phase change material is lauric acid, the first conductive filler is carbon black with a size of 100-200 nm, the second conductive filler is graphene with a sheet size of 5-10 um, the defoamer is polyoxyethylene oxypropylene glycerol, the thickener is sodium carboxymethyl cellulose, and the organic solvent is acetone.
[0104] In an embodiment of the present invention, a method for preparing a constant temperature heating film for enhancing the reproducibility of the PTC effect comprises the following steps: the size of the first conductive filler is preferably 50-400nm, and the size of the second conductive filler is preferably 1-70um
[0105] S1. Weigh 15 g of thermoplastic polyurethane elastomer and add it to 30 ml of acetone. Stir mechanically until there are no particles in the solvent. The stirring time is 60 min.
[0106] S2, weigh 5g of epoxy resin, add it, and stir it mechanically under water bath heating to make it fully cross-linked with the thermoplastic polyurethane elastomer, and the reaction time is 2h;
[0107] S3, weigh 7.5g of lauric acid, 6g of carbon black and 1g of layered graphene, add them to S2, and mix them by high-speed mechanical stirring for 45min;
[0108] S4, weigh 0.15g of polyoxyethylene oxypropylene glycerol and 0.35g of sodium carboxymethyl cellulose and add them to the mixed solution of S3 in sequence, adjust the viscosity of the solution to make it smooth, and disperse it with mechanical stirring until it is completely uniform, and the stirring time is 20min;
[0109] S5. Use a coating machine to coat the mixed solution obtained in step S4 on the polyimide film containing the copper electrode, that is, the lower layer of the insulating isolation layer, and obtain a positive temperature coefficient coating after drying. The coating thickness is controlled to be 0.5 mm.
[0110] S6. The lower insulating isolation layer and the upper insulating isolation layer containing the positive temperature coefficient coating are hot pressed and packaged to obtain a PTC heating film; wherein the single layer thickness of the insulating isolation layer is 1.5 mm, and the hot pressing treatment process is: hot pressing temperature 80°C, pressure 1MPa.
[0111] In the above steps, the speed of mechanical stirring was 2000 rpm, the stirring temperature was 80° C., and the viscosity of the solution was adjusted to 1500 mPa`s.
[0112] In the present embodiment, the epoxy resin is a polymer compound composed of an epoxy group (-COC-), which has high reactivity and can react with the active groups of the thermoplastic polyurethane elastomer, amino (-NH2), isocyanate group (-NCO) or hydroxyl (-OH). After the addition reaction occurs, the amino group in the thermoplastic polyurethane elastomer will form a covalent bond with the epoxy resin to form a cross-linked chemical structure. Consistent with Example 1, the cross-linked network structure formed by the two-phase matrix limits the size of the aggregates formed, and mixing fillers of different sizes can improve the dispersibility and inhibit the same fillers from tending to agglomerate. The synergistic effect of the two further enhances the reproducibility of the PTC effect of the heating film.
[0113] The PTC heating film of Example 4 was tested for cycle performance. The results are as follows: Figure 8 shown.
[0114] Figure 8 The PTC characteristic diagram of the PTC heating film obtained in Example 4 after 500 high and low temperature shock cycles; Figure 8It can be seen that the PTC heating film can still maintain a good PTC effect after 500 high and low temperature impact cycle tests, and the resistance-temperature curve does not change much, showing good reproducibility of the PTC effect.
[0115] Comparative Example 1
[0116] A constant temperature heating film for enhancing the reproducibility of the PTC effect, comprising the following components in percentage by mass: 30wt% thermoplastic polyurethane elastomer, 20wt% organic phase change material, 17wt% first conductive filler, 1wt% second conductive filler, 0.5wt% defoamer, 1.5wt% thickener, and 30wt% organic solvent; wherein the phase change material is lauric acid, the first conductive filler is carbon black with a size of 100-200nm, the second conductive filler is carbon nanotube with a size of 30-50um, the defoamer is polydimethylsiloxane, the thickener is sodium carboxymethyl cellulose, and the organic solvent is isophorone. The size of the first conductive filler is preferably 50-400nm, and the size of the second conductive filler is preferably 1-70um
[0117] A method for preparing a constant temperature heating film for enhancing the reproducibility of a PTC effect comprises the following steps:
[0118] S1. Weigh 24 g of thermoplastic polyurethane elastomer and add it to 48 ml of isophorone. Disperse it with mechanical stirring until there are no particles in the solvent. The stirring time is 45 min.
[0119] S2, weighing 16 g of lauric acid, 13.6 g of carbon black and 0.8 g of carbon nanotubes, adding them to the product obtained in step S1, and mixing them by high-speed mechanical stirring for 30 min;
[0120] S3, weighing 0.4g of polydimethylsiloxane and 1.2g of sodium carboxymethyl cellulose, and adding them to the mixed solution obtained in step S2 in sequence, adjusting the viscosity of the solution to make it smooth, and mechanically stirring and dispersing until it is completely uniform, and the stirring time is 25min;
[0121] S4, using a coating machine to coat the mixed solution obtained in step S3 on the polyimide film containing the copper electrode, i.e., the lower layer of the insulating isolation layer, to obtain a positive temperature coefficient coating after drying, and the coating thickness is controlled to be 1 mm;
[0122] S5. The lower insulating isolation layer and the upper insulating isolation layer containing the positive temperature coefficient coating are hot pressed and packaged to obtain a PTC heating film; wherein the single layer thickness of the insulating isolation layer is 0.5 mm, and the hot pressing process is: hot pressing temperature 80°C, pressure 1MPa.
[0123] In the above steps, the speed of mechanical stirring was 1800 rpm, the stirring temperature was 70° C., and the viscosity of the solution was adjusted to 1500 mPa`s.
[0124] The performance test of the non-crosslinked PTC heating film of Comparative Example 1 was carried out, and the results are as follows: Figure 9-11 shown.
[0125] in, Fig. 9 60 times of power-on-temperature rise curve of the PTC heating film obtained in this comparative example 1; Fig. 9 It can be seen that after only 60 power-on and heating cycles, the equilibrium temperature of the non-cross-linked PTC heating film dropped from 40.3°C to 39.2°C, with a temperature difference of 1.1°C.
[0126] Fig.10 This is a uniform heating diagram of the surface of the PTC heating film obtained in this comparative example 1 after 60 times of power-on heating; Fig.10 It can be seen that the surface heating uniformity of the uncross-linked PTC heating film for the 60th time is significantly different from that for the 1st time, and a large area of heating weakening has occurred. This is because the conductive filler is prone to agglomeration in the large phase area during multiple heating cycles, resulting in uneven heating.
[0127] Fig.11 The SEM comparison diagram of the PTC heating film obtained in Comparative Example 1 and Example 1; Fig.11 It can be seen that, relative to the PTC heating film obtained in Comparative Example 1, the PTC heating film obtained in Example 1 has a rich cross-linked network structure and a finer internal space. Specifically, during the temperature cycle of the PTC heating film, under the driving force of thermodynamic incompatibility, aggregates are easily formed between the same fillers, and the conductive phase with a larger phase size can provide a wide space for the conductive filler, which will lead to the formation of larger filler aggregates, so that the reproducibility of the PTC effect is negatively affected. Therefore, the selection of hybrid fillers of different sizes can not only improve the dispersion of the filler but also reduce the possibility of agglomeration of similar fillers. Moreover, the conductive phase with a smaller phase size means that the movement of the conductive filler in a narrow space is inhibited, which limits the maximum size of the filler aggregate to a certain extent, and the small aggregates are easier to disassemble after formation. In short, the cross-linked structure and filler hybridization are used to synergistically improve the agglomeration phenomenon of the conductive filler, so as to enhance the reproducibility of the PTC effect.
[0128] Compared with Example 1, the heating capacity of the PTC heating film obtained in this comparative example 1 is significantly worse than that of the PTC heating film obtained in Example 1 after multiple power-on uses. Before 100 uses, large-area heat reduction and a widening gap in the final equilibrium temperature appeared, which further confirms that the cross-linked structure and mixed fillers of different sizes in the present invention can improve the agglomeration phenomenon, ensure the heating stability of the PTC heating film and extend its service life.
[0129] In this embodiment, the obtained positive temperature coefficient slurry is smooth and has no granular feeling. When the slurry is coated on the polyimide film with copper-clad electrodes, the surface of the film is smooth and not rough after drying, and it has good flexibility and can be bent arbitrarily; the PTC film heats up evenly, indicating that the temperature control performance of the PTC heating film is excellent and stable; because the positive temperature coefficient coating under the invention has a relatively rich cross-linked network structure, the PTC film can maintain good PTC effect reproducibility in multiple repeated thermal cycles.
[0130] It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the above embodiments without departing from the principles of the present invention, and these improvements and modifications should also be regarded as within the protection scope of the present invention.
Claims
1. A constant temperature heating film for enhancing the reproducibility of the PTC effect, comprising two insulating isolation layers, a copper electrode arranged between the insulating isolation layers, and a positive temperature coefficient coating, wherein the copper electrode is etched on the upper end of the lower insulating isolation layer, and the positive temperature coefficient coating is coated on the upper end of the copper electrode; characterized in that: The positive temperature coefficient coating comprises the following components: 15-30wt% thermoplastic polyurethane elastomer, 5-20wt% secondary phase matrix, 10-40wt% organic phase change material, 14-25wt% first conductive filler, 1-5wt% second conductive filler, 0.1-1wt% defoamer, 0.5-2wt% thickener, 30-50wt% organic solvent; the secondary phase matrix is one of isocyanates, peroxides, polyhydroxy compounds and epoxy compounds; the particle size of the first conductive filler is 100-300nm, and the particle size of the second conductive filler is 5-50um.
2. The constant temperature heating film for enhancing the reproducibility of the PTC effect according to claim 1, characterized in that: The isocyanates are diphenylmethane diisocyanate, toluene diisocyanate and hexamethylene diisocyanate; the peroxides are dibenzoyl peroxide and diisophorone peroxide; the polyhydroxy compounds include glycerol, ethylene glycol and polyethylene glycol; and the epoxy compound is epoxy resin.
3. The constant temperature heating film for enhancing the reproducibility of the PTC effect according to claim 1, characterized in that: The organic phase change material is at least one of paraffin, fatty acid and polyol.
4. The constant temperature heating film for enhancing the reproducibility of the PTC effect according to claim 3, characterized in that: The fatty acids are stearic acid, palmitic acid, myristic acid and lauric acid; the polyols are polyethylene glycol and tetradecanol.
5. The constant temperature heating film for enhancing the reproducibility of the PTC effect according to claim 1, characterized in that: The first conductive filler is at least one of conductive carbon black and metal powder; the second conductive filler is at least one of carbon nanotubes, carbon fibers and graphene.
6. The constant temperature heating film for enhancing the reproducibility of the PTC effect according to claim 1, characterized in that: The defoaming agent includes at least one of silicone oil defoaming agent, polyvinyl alcohol defoaming agent or polyester defoaming agent; the thickener is at least one of ethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the organic solvent is at least one of toluene, xylene, isophorone, n-hexane and acetone.
7. The constant temperature heating film for enhancing the reproducibility of the PTC effect according to claim 1, characterized in that: The two insulating isolation layers are both polyimide films; the thickness of the insulating isolation layer is 0.5-2mm; the thickness of the positive temperature coefficient coating is 0.5-2mm; the constant temperature heating film for enhancing the reproducibility of the PTC effect has a resistivity of 1-50Ω·cm at room temperature.
8. The method for preparing a constant temperature heating film with enhanced PTC effect reproducibility according to any one of claims 1 to 7, characterized in that The steps include: S1, adding a thermoplastic polyurethane elastomer into an organic solvent, and stirring and dispersing the thermoplastic polyurethane elastomer into an organic solvent until the elastomer is free of particles; S2, adding the secondary phase matrix to the product obtained in step S1, heating in a water bath and stirring for cross-linking reaction for 1-2 hours; S3, adding the organic phase change material, the first conductive filler and the second conductive filler to the product obtained in step S2 and stirring and mixing them evenly; S4, adding the defoamer and thickener to the mixed solution of step S3, stirring and dispersing them evenly; S5, using a coating machine to coat the mixed solution obtained in step S4 on the lower insulating isolation layer with a copper electrode etched on the upper end, and drying; S6. The lower insulating isolation layer and the upper insulating isolation layer are heat-pressed and packaged to obtain a constant temperature heating film with enhanced reproducibility of the PTC effect.
9. The method for preparing a constant temperature heating film with enhanced PTC effect reproducibility according to claim 8, characterized in that: In steps S1-S4, the stirring is mechanical stirring, the speed is 1000-2400rmp, and the temperature is 60-90°C; wherein the time for stirring and dispersing in step S1 until there are no particles in the solvent is 30-60min; the time for stirring in step S3 is 30-60min; the time for stirring in step S4 is 20-30min; The temperature of the hot pressing bonding is 60-100° C., and the pressure is 0.5-1 MPa.
10. Use of the constant temperature heating film with enhanced PTC effect reproducibility as claimed in any one of claims 1 to 7 in the preparation of temperature control components.
Citation Information
Patent Citations
PTC composite material heating film and manufacturing method and application thereof
CN103476158B
Automatic temperature control electric heating film, and preparation method and application thereof
CN112770422A
Constant-temperature heater for satellite and manufacturing method of constant-temperature heater
CN116133170A
High-strength wear-resistant thermoplastic polyurethane elastomer as well as preparation method and application thereof
CN117801214A
Preparation method of stretchable graphene conductive ink and flexible graphene electrothermal film
CN117844309A